2018
DOI: 10.1097/md.0000000000009747
|View full text |Cite
|
Sign up to set email alerts
|

The association of single nucleotide polymorphism rs189037C>T in ATM gene with coronary artery disease in Chinese Han populations

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…NLRC4 and NCL contain genetic variants associated with inflammation biomarkers [ 28 , 29 ]. Genetic variants in PTEN and ATM genes have been associated with eosinophil count [ 30 ] and CHD [ 31 ], respectively. Finally, differential methylation in cg06642177 linked to SKG1 has been previously associated with myocardial infarction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLRC4 and NCL contain genetic variants associated with inflammation biomarkers [ 28 , 29 ]. Genetic variants in PTEN and ATM genes have been associated with eosinophil count [ 30 ] and CHD [ 31 ], respectively. Finally, differential methylation in cg06642177 linked to SKG1 has been previously associated with myocardial infarction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…D’Ascenzo et al found that the inhibition of STAT3 phosphorylation attenuated ischemia–reperfusion injury during interventional therapy for acute coronary syndrome ( 38 ). Additionally, in Chinese Han populations, the ATM rs189037 polymorphism is associated with coronary artery disease (CAD), and the rs189037 genotype seems to be associated with a lower risk of CAD and is a protective genetic marker of CAD, particularly in males and smokers ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a regulator of oxidative stress and sensor of DNA damage, ATM gene prevents cellular senescence, death, or cell cycle arrest; in addition, it protects individuals from ROS-induced DNA damage. Ding et al have described an association of SNP rs189037 in ATM gene with the proportion of coronary artery disease in Chinese Han population and demonstrated a low proportion of coronary artery disease in participants harboring TT genotype ( 21 ). In the current study, the young and centenarian participants showed significantly lower frequency of mutant rs189037 in ATM gene than middle-aged and elderly participants.…”
Section: Discussionmentioning
confidence: 99%